3D Cell Printing of Functional Skeletal Muscle Constructs Using Skeletal Muscle‐Derived Bioink. Issue 20 (16th August 2016) - Choi, Yeong‐Jin; Kim, Taek Gyoung; Jeong, Jonghyeon; Yi, Hee‐Gyeong; Park, Ji Won; Hwang, Woonbong; Cho, Dong‐Woo
Abstract : Engineered skeletal muscle tissues that mimic the structure and function of native muscle have been considered as an alternative strategy for the treatment of various muscular diseases and injuries. Here, it is demonstrated that 3D cell‐printing of decellularized skeletal muscle extracellular matrix (mdECM)‐based bioink facilitates the fabrication of functional skeletal muscle constructs. The cellular alignment and the shape of the tissue constructs are controlled by 3D cell‐printing technology. mdECM bioink provides the 3D cell‐printed muscle constructs with a myogenic environment that supports high viability and contractility as well as myotube formation, differentiation, and maturation. More interestingly, the preservation of agrin is confirmed in the mdECM, and significant increases in the formation of acetylcholine receptor clusters are exhibited in the 3D cell‐printed muscle constructs. In conclusion, mdECM bioink and 3D cell‐printing technology facilitate the mimicking of both the structural and functional properties of native muscle and hold great promise for producing clinically relevant engineered muscle for the treatment of muscular injuries. Abstract : Skeletal muscle‐derived bioink with 3D cell‐printing technology facilitates the fabrication of 3D functional muscle constructs. 3D cell‐printing technology can generate various types of constructs and cellular alignments in a controlled manner. The bioink retains the major extracellular matrix molecules that provide a microenvironment similar to that of native muscle and induce myogenesis in 3D cell‐printed muscle constructs.